2021
DOI: 10.3389/fagro.2021.753474
|View full text |Cite
|
Sign up to set email alerts
|

Do Bioinoculants Affect Resident Microbial Communities? A Meta-Analysis

Abstract: There is a global industry built upon the production of “bioinoculants,” which include both bacteria and fungi. The recent increase in bioinoculant uptake by land users coincides with a drive for more sustainable land use practices. But are bioinoculants sustainable? These microbes are believed to improve plant performance, but knowledge of their effect on resident microbial communities is scant. Without a clear understanding of how they affect soil microbial communities (SMC), their utility is unclear. To ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…As a result, there is mounting effort to increase the aboveground macrobiological diversity of our managed landscapes. Despite these lessons from aboveground ecosystems, there is increasing danger of repeating the mistakes of macrobiological agriculture at the micro scale, with consequences for indigenous microbial taxa 100 . For example, given the potential of microbial inoculations to promote plant productivity, there is an exploding landscape of microbial inoculant companies advocating for the large-scale application of single species or very low-diversity non-native microbial consortia.…”
Section: Manage: Managed Ecosystems As Reservoirs Of Microbial Diversitymentioning
confidence: 99%
“…As a result, there is mounting effort to increase the aboveground macrobiological diversity of our managed landscapes. Despite these lessons from aboveground ecosystems, there is increasing danger of repeating the mistakes of macrobiological agriculture at the micro scale, with consequences for indigenous microbial taxa 100 . For example, given the potential of microbial inoculations to promote plant productivity, there is an exploding landscape of microbial inoculant companies advocating for the large-scale application of single species or very low-diversity non-native microbial consortia.…”
Section: Manage: Managed Ecosystems As Reservoirs Of Microbial Diversitymentioning
confidence: 99%
“…Is legacy a benefit or a risk? Microbial inoculants often leave a footprint in the recipient soil (Mawarda et al, 2020; Cornell et al, 2021), while such legacy effect in reshaping soil microbiome is largely overlooked (Liu et al, 2022). Although studies with single-strain and consortium inoculations have shown that the effects of inoculum on soil microbial communities can be significant, at least in the short term (e.g., tens of days) (Mallon et al, 2018; Wang et al, 2018; Xing et al, 2021), the long-term resilience of microbial community composition and the mechanism of its resistance against inoculations remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An effective bioinoculant must impact the species already present in the soil, particularly the plant pathogens [ 89 ]. Therefore, introducing bioinoculants into an agroecosystem creates the need to assess their impact on the soil native microbiome and estimate their efficacy against the populations of plant pathogens.…”
Section: Methods For Evaluating the Effect On The Soil Microbiome To ...mentioning
confidence: 99%
“…Therefore, introducing bioinoculants into an agroecosystem creates the need to assess their impact on the soil native microbiome and estimate their efficacy against the populations of plant pathogens. The answer to such questions also averts undesirable effects, such as an excessive impoverishment of natural biodiversity or competition with fungal or bacterial species whose presence is desirable for crops, such as certain mycorrhizal fungi or nitrogen-fixing bacteria [ 89 , 90 ]. Nevertheless, the physiological characteristics of the bioinoculum determine to a great extent its survival/fate and activity in the soil and biotic/abiotic soil factors are also major factors affecting the persistence/decline of a microbial inoculant population introduced in the soil as well as its contribution to the provision of ecosystem services [ 91 ].…”
Section: Methods For Evaluating the Effect On The Soil Microbiome To ...mentioning
confidence: 99%